Applying genetic algorithm for optimization income value - Siagian, Ayu Febri; Yanris, Gomal Juni; Sitorus, Sahat Parulian (Politeknik Ganesha Medan, 2022)
In this digital era, the use of information technology and internet technology cannot be separated from digital services. Starting from product promotion media, recording customer data, determining the amount of revenue from product sales, and optimizing the value of revenue. Sales of digital service products owned by PT. XYZ needs to be evaluated to find out which products are most in demand by customers from each product offering that has been made. Therefore we need a system to calculate revenue from the number of customers who use the product for further promotion. The object of this research focuses on optimizing the value of income at PT. XYZ of the products they market, the results of the object will be used as an evaluation to determine a new strategy in carrying out promotions for products that are less attractive to customers. The data used in this study is customer data for January 2017-December 2021. The method used in this study uses a genetic algorithm to determine the optimization of the revenue value. For the optimization results, the genetic algorithm went well, because it resulted in a smaller comparison of error values ​​compared to values ​​that were not optimized. The error value in January 2019 with a non-optimized value was 35,498.8 and the optimized value got an error value of 32,364.9. The results of this study are used as a sales evaluation to increase promotions on digital services that are less attractive to customers. In addition, the results of the application of this genetic algorithm method can provide a better solution to increase income in the next period.